Deferred Maintenance of Public University Buildings in Malaysia: A Preliminary Study - Yasin, Mohd Norazam; Mairizal; Mohamad Zin, Rosli; Hamid, Md Yusof; Wahi, Noraziah; Hammad, Dabo Baba; Syed Mohamad, Syed Burhanuddin Hilmi; Zakaria, Mohd Azuan (International Journal of Integrated Engineering, 2022)
Deferred maintenance has become a universal issues in most developing countries and adversely affects the administration of an organization. A building must be well maintained in order to provide optimal operation in service and it is vital because it affected the performance of the buildings. Public university buildings are a factor of production, they are producing the future leaders, managers, engineers and industry players. Hence, this study is intended to identify the issues and challenges and also causes and effects of deferred maintenance of public university buildings in Malaysia. In order to achieved that, a preliminary expert interview was conducted in this research is to identify rich information and to explore the topic comprehensively from participants and also to obtain initial information and understanding before further study is continued. Preliminary expert interviews are necessary to help the researcher to refine, rephrase and confirm the factors derived from the literature. An interviews were carried out amongst selected experienced personnel for expert opinion to identify the significant issues and challenges and also causes and effects of deferred maintenance of public university buildings in Malaysia. Seven respondents were selected from professional industrial and academician involved in building maintenance management. The study will reveal the issues and challenges and also causes and effects and provide useful information and better knowledge of the deferred maintenance.